Increasing Trend of Antimicrobial Drug-Resistance in Pseudomonas aeruginosa Causing Septicemia - R Moniri; Z Mosayebi; AH Movahedian (Tehran University of Medical Sciences, 2006)
The emergence of multi-drug resistant strains of Pseudomonas aeruginosa has complicated treatment decision and may lead to treatment failures. In this study, we describe the trends of drug-resistant P. aeruginosa isolated in blood cultures from patients detected in a tertiary teaching hospital and evaluated the prevalence of resistance to amikacin, ampicillin, carbeni- cillin, cefixime, cefotaxime, ceftazidime, ceftizoxime, ceftriaxone, gentamicin, imipenem, and trimethoprim/ sulfameth- oxazole in sixty-nine strains of P. aeruginosa isolated from neonates with septicemia in Kashan, Iran, from April, 2000 to June 2004. In assessment of the current breadth of multi-drug resistance in P. aeruginosa isolated from neonates with septicemia, 4.3% were susceptible to all studied agents, 10.1% were resistant to a single agent. Multi-drug resistance (MDR) isolates accounted for 73.9% of isolates. The majority of MDR isolates (41.2%) were resistant to three antimicrobial agents, which accounted for 30.4% of all isolates. Nineteen MDR isolates from fifty-one (37.3%) were resistant to four agents (19 out of 69; 27.5% of all isolates) and 21.6% to five agents (15.9% of all isolates). Statistical analysis confirmed that there were no significant differences between multi-drug resistance phenotypes of isolates with age, gender, gestational age, outcome of septicemia, and application of respirator in neonates. Continued local surveillance studies are urged to monitor emerging antimicrobial resistance and to guide interventions to minimize its occurrence.